2021
DOI: 10.1016/j.celrep.2021.108689
|View full text |Cite
|
Sign up to set email alerts
|

NIX initiates mitochondrial fragmentation via DRP1 to drive epidermal differentiation

Abstract: SUMMARY The epidermis regenerates continually to maintain a protective barrier at the body’s surface composed of differentiating keratinocytes. Maturation of this stratified tissue requires that keratinocytes undergo wholesale organelle degradation upon reaching the outermost tissue layers to form compacted, anucleate cells. Through live imaging of organotypic cultures of human epidermis, we find that regulated breakdown of mitochondria is critical for epidermal development. Keratinocytes in the upp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 96 publications
5
39
0
Order By: Relevance
“…However, another work proposes a predominating role of mitochondrial-derived ROS in basal KCs as a signal to induce differentiation [ 41 ]. This is in line with a recent report showing that NIX, a transcription factor located in mitochondria, controls mitophagy and, in turn, KC differentiation, hence emphasizing the role of mitochondria in KC fate [ 42 ]. Thus, further work is required to clarify the relative contribution of glycolysis versus oxidative phosphorylation (OXPHOS) in the control of homeostatic processes in the epidermis.…”
Section: Metabolic Features Of Keratinocytes In Normal Skinsupporting
confidence: 91%
“…However, another work proposes a predominating role of mitochondrial-derived ROS in basal KCs as a signal to induce differentiation [ 41 ]. This is in line with a recent report showing that NIX, a transcription factor located in mitochondria, controls mitophagy and, in turn, KC differentiation, hence emphasizing the role of mitochondria in KC fate [ 42 ]. Thus, further work is required to clarify the relative contribution of glycolysis versus oxidative phosphorylation (OXPHOS) in the control of homeostatic processes in the epidermis.…”
Section: Metabolic Features Of Keratinocytes In Normal Skinsupporting
confidence: 91%
“…To confirm the regulation of BNIP3L by miR-30a in a more relevant system, we took advantage of an organotypic model of RHE generated from HPK overexpressing miR-30a. Using three different human donors, we showed that keratinocytes normally express BNI3PL in the granular layer of the epidermis (Figure 2A), in accordance with its described function in the degradation of mitochondria during the cornification (Simpson et al, 2021). Strikingly, the overexpression of miR-30a in keratinocytes induced a strong reduction of BNIP3L staining in the granular layer.…”
Section: Mir-30a-5p Abolishes Bnip3l Expression In the Granular Layer Of Rhesupporting
confidence: 67%
“…In the epidermis, autophagy is constitutively active in the granular layer, where nuclei are cleared, leading to the terminal differentiation (Akinduro et al, 2016). In addition, mitophagy, a specialized type of autophagy that targets mitochondria for elimination, is a key step to activate the terminal differentiation of keratinocytes, through the BNIP3/BNIP3L (also known as NIX) pathway (Monteleon et al, 2018;Moriyama et al, 2014;Simpson et al, 2021). Interestingly, autophagy is a recurrent biological pathway targeted by miR-30 family in others systems, especially in many types of cancers (Pourhanifeh et al, 2020;Yang et al, 2021;Zhu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Upon phosphorylation, these receptors interact with phagophore proteins such as LC3 and Gabarap [ 189 , 191 , 196 ]. In the early stages of mitophagy, Bnip/Nix also promote the mitochondrial localization of Drp1, which would enhance fission and aid in Parkin recruitment, leading to mitophagy [ 197 , 198 , 199 ].…”
Section: Regulation Of Mitophagy In Musclementioning
confidence: 99%